Plasma Vitamin B12 Levels, High-Dose Vitamin B12 Treatment, and Risk of Dementia - Arendt, Johan Frederik Håkonsen (J Alzheimers Dis, 2021)
BACKGROUND: It is controversial whether B12 deficiency causes dementia or B12 treatment can prevent dementia. OBJECTIVE: To assess associations between low plasma (P-)B12 levels, B12 treatment, and risk of Alzheimer’s disease (AD; primary outcome) and all-cause or vascular dementia (secondary outcomes). METHODS: We conducted a population-based cohort study using Danish registry data to assess associations between low P-B12 levels, high-dose injection or oral B12 treatment, and risk of dementia (study period 2000–2013). The primary P-B12 cohort included patients with a first-time P-B12 measurement whose subsequent B12 treatment was recorded. The secondary B12 treatment cohort included patients with a first-time B12 prescription and P-B12 measurement within one year before this prescription. For both cohorts, patients with low P-B12 levels (<200 pmol/L) were propensity score-matched 1:1 with patients with normal levels (200–600 pmol/L). We used multivariable Cox regression to compute 0–15-year hazard ratios for dementia. RESULTS: For low P-B12 and normal P-B12 level groups, we included 53,089 patients in the primary P-B12 cohort and 13,656 patients in the secondary B12 treatment cohort. In the P-B12 cohort, hazard ratios for AD centered around one, regardless of follow-up period or treatment during follow-up. In the B12 treatment cohort, risk of AD was unaffected by low pre-treatment P-B12 levels, follow-up period and type of B12 treatment. Findings were similar for all-cause and vascular dementia. CONCLUSION: We found no associatio1n between low P-B12 levels and dementia. Associations were unaffected by B12 treatment. Results do not support routine screening for B12 deficiency in patients with suspected dementia.